High-performance and recyclable epoxy resins based on fully bio-based hardeners containing Schiff base structures - Ruize Zhang; Jiaqi Zhong; Gaosheng Wu; Kaidi Xu; Xiaoli Xu; Xuliang Cui; Baoyun Xu; Xiaolei li (Royal Society Open Science, 2025)
The development of recyclable bio-based epoxy resins has been the focus of research nowadays, particularly in light of increasing environmental concerns and the drive for resource recycling. Herein, two fully bio-based epoxy curing agents, VLYS (fully bio-based Schiff basic epoxy curing agent based on vanillin and lysine) and VLEV (fully bio-based Schiff basic epoxy curing agent based on vanillin and levodopa), were synthesized by reacting amino acids—lysine and levodopa, respectively—with vanillin. Both epoxy resins cured by these two hardeners, VLYS-E and VLEV-E, show high glass transition temperatures (Tg > 141°C) and superior mechanical properties (Young’s modulus >1000 MPa and flexural modulus >2900 MPa), which are far better than the resin system based on a petroleum-based curing agent. The incorporation of the Schiff base endows these resins with degradability and reprocessability, while exhibiting high-percentage retention of thermal and mechanical properties after two cycles. Taken together, these findings suggest that these fully bio-based curing agents hold significant potential to supplant conventional hardeners.